The modern art invasion : Picasso, Duchamp, and the 1913 Armory Show that scandalized America - Lunday, Elizabeth (Lyons Press, 2013)
"The story behind the 1913 Armory Show, the most important art exhibit in U.S. history. Held a century ago, in the winter of 1913, the show brought Modernism to America in an unprecedented display of 1300 works by artists including Picasso, Matisse, and Duchamp. Drawing from primary sources and setting the Armory Show into the context of American culture just before World War I, the book brings the exhibition and its era to vivid life"--